Varicella Vaccination During Early Pregnancy: A Cause of in utero Miliary Fetal Tissue Calcifications and Hydrops? - Joseph Apuzzio; Vijaya Ganesh; Leslie Iffy; Anthony Al-Khan (Hindawi Limited, 2002)
Background: It is the purpose of this article to describe a suspected association of inadvertent vaccination with varicella vaccine during early pregnancy with the subsequent development of in utero miliary fetal tissue calcifications and fetal hydrops detected by sonogram at 15 weeks of gestation.